Consumer innovation in the poor versus rich world: Some differences and similarities - Sarah Praceus; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2012)
Innovative, distinct products and no cheaper copies of the rich world are essential in order to succeed at the Base of the Pyramid (BoP). However, this type of innovation requires more, in-depth information on the BoP and solution spaces, which are both difficult to access. Literature proposes to generate innovations bottom up through user involvement but remains silent on how to identify and integrate BoP consumers into the innovation process. One obvious solution is to connect up with and cooperate with innovating consumers of the BoP. However, this raises the questions whether 1) user innovation exists at the BoP at what levels of quality and 2) how firms can support the innovators to implement them into real world solutions. In this paper we specifically address the first question and analyze patterns and characteristics of a large sample of innovations developed by people living at the Indian BoP collected by the Indian National Innovation Foundation (NIF). We compare these innovations to consumer innovations in the developed world and examine effects of demographic, knowledge and context factors on innovation activity and the outcome. We find similarities with consumer innovation in the developed world and at the same time adaptations to the BoP context, e.g. fulfillment of rather basic necessities than hobby-related needs. Innovation quality is mostly driven by the innovator's knowledge and market recognition is highest for creative innovations developed for others. The paper further shows that consumer innovations are a good starting point for firms seeking solutions for BoP markets. Product needs can be systematically deducted and provide insights on how to identify promising consumer innovators at the BoP. Finally, this research contributes to better understand user innovation behavior in a specific context and by that enriches innovation research.
Keywords: 650